Human resource management (HRM) practices and employee job satisfaction: The case of a public corporation in Qatar - Al-Marri, Baina Hamad (Journal of Economic, Administrative and Legal Sciences, 2024)
The main purpose of this research is to investigate the impact of HRM practices (training and development, and performance management practices) on employee satisfaction in case of a public corporation in Qatar.  The research was carried out into the first quarter of 2024. To meet the main and sub objectives of the research, a survey questionnaire was developed and distributed to a simple random sample of (92) employees, who work for a public corporation in Qatar. The total number of the returned surveys was (78) surveys. This means that the response rate was 84%. The data was analyzed by using SPSS. Results of data analysis revealed that.1. Respondents are highly satisfied with their jobs at the selected Qatari public corporation. 2. Respondents at the selected Qatari public corporation positively perceive HRM practices (training and development, and performance management practices).3. There is a positive and strong correlation between training and development, and performance management practices, on one hand and employee job satisfaction, on the other hand. 4. The impact of training and development on employee job satisfaction is bigger than the impact of performance management.5. Training and development practices explain 22% of employee job satisfaction, performance management practices explain 19% of employee job satisfaction. Based on that, it was suggested to:1. Foster HRM practices to foster employee job satisfaction. 2. Invest heavily in HR, through enhancing training and development practices.3. Continually review and improve performance appraisal practices to be more effective.  4. Carry out future research to investigate other factors that may drive employee job satisfaction.
Keywords: HRM practices; Job satisfaction; Training and development; Performance management